Planar slot antenna with circular and vertical polarization diversity. Issue 10 (October 2017) - Lawrence, Nicholas P.; Abbott, Derek
Abstract: This article proposes an easily manufacturable multifunction two‐port planar slot antenna, radiating omnidirectional linearly polarized and broadside circularly polarized radiation patterns through a common slot in an overlapping frequency bandwidth at 5.9 GHz of 2.56%, with inter‐port coupling below −45 dB.